Comparison of the bone marrow trephine sample quality between OnControl drill system and the Jamshidi needle. (19th February 2019) - Forwood, Kathryn M.; Lee, Edwin; Crispin, Philip J.
Abstract: Introduction: Bone marrow biopsies are a key diagnostic and monitoring intervention in haematology with manual bone marrow techniques the established method of choice. Powered biopsy devices are now available, but are not widely used in haematology. This study compared the quality of bone marrow trephines obtained with the Jamshidi needle and OnControl powered drill system. Methods: Retrospective analysis was undertaken on trephine samples prior to and after implementation of the OnControl drill system. Trephine size and quality were assessed independently by three pathologists and compared between techniques and operators using nonparametric tests. Results: There were 164 samples assessed (Jamshidi n = 69, OnControl, same site as aspirate n = 48, OnControl, separate site from aspirate n = 47). The assessable and total length were similar between the Jamshidi and OnControl techniques, with increased crush artefact observed with the OnControl drill ( P  < 0.001). Using a separate puncture site for trephine collection and aspirate did not reduce the artefact seen with the OnControl system ( P  = 0.274). Smaller samples ( P  < 0.001) and an increase in crushed ( P  = 0.009) and connective tissue ( P  = 0.002) were seen in trephines obtained by nonlaboratory‐based trainees, regardless of the needle used or their stage of training, compared to laboratory trainees. Conclusions: Trephines obtained by either method had similar assessable areas. The OnControl system was associated with more artefact, a finding in line with previous studies. There was no improvement by sampling the trephine from a separate site to the aspirate. Laboratory‐based trainees who reviewed marrow morphology produced trephines with better assessable length than those not based in the laboratory.